Answer:
B
Step-by-step explanation:
To rewrite the equation x + y + 3 = -2x + 4y + 18, first combine like terms.
x + y + 3 = -2x + 4y + 18
3x - 3y + 3 = 18
3x - 3y = 15
This is the standard form.
It can also be simplified by dividing each term by 3 to x - y = 5.
11 seconds behind after 22 days
The answer would be true because 4+5 is > 8
well, clearly the LCD from the denominators of 5 and 10 is just 10, thus
![\bf \stackrel{\textit{Sue}}{\cfrac{2}{5}}+\stackrel{\textit{Sally}}{\cfrac{4}{10}}\implies \stackrel{\textit{LCD of 10}}{\cfrac{(2)2~~+~~(1)4}{10}}\implies \cfrac{2+4}{10}\implies \cfrac{6}{10}\implies \stackrel{\textit{simplified}}{\cfrac{3}{5}}](https://tex.z-dn.net/?f=%5Cbf%20%5Cstackrel%7B%5Ctextit%7BSue%7D%7D%7B%5Ccfrac%7B2%7D%7B5%7D%7D%2B%5Cstackrel%7B%5Ctextit%7BSally%7D%7D%7B%5Ccfrac%7B4%7D%7B10%7D%7D%5Cimplies%20%5Cstackrel%7B%5Ctextit%7BLCD%20of%2010%7D%7D%7B%5Ccfrac%7B%282%292~~%2B~~%281%294%7D%7B10%7D%7D%5Cimplies%20%5Ccfrac%7B2%2B4%7D%7B10%7D%5Cimplies%20%5Ccfrac%7B6%7D%7B10%7D%5Cimplies%20%5Cstackrel%7B%5Ctextit%7Bsimplified%7D%7D%7B%5Ccfrac%7B3%7D%7B5%7D%7D)